2011
DOI: 10.1007/s10584-011-0107-8
|View full text |Cite
|
Sign up to set email alerts
|

Estimating coastal recession due to sea level rise: beyond the Bruun rule

Abstract: Accelerated sea level rise (SLR) in the twenty-first century will result in unprecedented coastal recession, threatening billions of dollars worth of coastal developments and infrastructure. Therefore, we cannot continue to depend on the highly uncertain coastal recession estimates obtained via the simple, deterministic method (Bruun rule) that has been widely used over the last 50 years. Furthermore, the emergence of risk management style coastal planning frameworks is now requiring probabilistic (rather than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
193
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(199 citation statements)
references
References 22 publications
5
193
0
1
Order By: Relevance
“…The quantification of the local probabilities of failure is input for any probabilistic dike safety assessment or probabilistic design. These results become even more relevant in cases of dike concepts such as the unbreachable dike and the multi-functional flood defence [51] which are designed to cope with climate change [5] and to withstand large amounts of overflow and storms similar or larger than the largest ones tested in this study.…”
Section: Applications Of the Probabilistic Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…The quantification of the local probabilities of failure is input for any probabilistic dike safety assessment or probabilistic design. These results become even more relevant in cases of dike concepts such as the unbreachable dike and the multi-functional flood defence [51] which are designed to cope with climate change [5] and to withstand large amounts of overflow and storms similar or larger than the largest ones tested in this study.…”
Section: Applications Of the Probabilistic Methodsmentioning
confidence: 83%
“…For rivers, extreme water levels occur more frequently as shown for the River Rhine basin [4], for example. Such climate change effects increase the risk of flooding of low lying, highly populated areas around world [5,6]. In the last decades, flood defence design has moved towards a risk-based approach [7,8] in which it is possible to express the design parameters uncertainty as probabilistic distributions [8].…”
Section: Introductionmentioning
confidence: 99%
“…Cooper and Pilkey (2004) concluded that the assumptions to be satisfied for applying this model are very restrictive and, in consequence it should only likely to be applicable on a small number of coasts. Ranasinghe et al (2012) proposed a probabilistic model based on governing physical processes to estimate coastal erosion (PCR) due to SLR. However, these authors explicitly stated that "several simplifying assumptions in the model need to be rigorously evaluated" and some elements of the model need to be defined using empirical evidence that are often absent (e.g.…”
Section: Shoreline Retreatmentioning
confidence: 99%
“…More importantly, this approach fails to include the dynamic response due to anthropogenic, ecologic 10 , or morphologic processes such as erosion and deposition-that drives coastal landscape evolution 11 . Dynamic response assessments 11,12 tend to represent cross-shore sediment transport processes explicitly with highly parameterized models, and can be used to make probabilistic assessments 13 via Monte Carlo methods and sensitivity analyses to communicate uncertainty 14 . Uncertainty affecting these approaches includes unknowns regarding rates and magnitudes of SLR, storminess, model parameter values, and the extrapolation from cross-shore profiles to spatially extensive domains.…”
mentioning
confidence: 99%